1996
DOI: 10.1074/jbc.271.40.24492
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Active Site of Type II Dehydroquinases

Abstract: A novel method based on electrospray mass spectrometry (Krell, T., Pitt, A. R., and Coggins, J. R. (1995) FEBS Lett. 360, 93-96) has been used to localize active site residues in the type I and type II dehydroquinases. Both enzymes have essential hyper-reactive arginine residues, and the type II enzymes have an essential tyrosine residue. The essential hyper-reactive Arg-23 of the Streptomyces coelicolor type II enzyme has been replaced by lysine, glutamine, and alanine residues. The mutant enzymes were purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Therefore we would expect that inhibition would not be as strong as that seen in the S. coelicolor enzyme. The presence of a second sulphate interacting with residues in part of the lid domain, in particular Arg19, a residue already shown to be important for catalysis [8], may help to explain the increase in V max seen in the presence of phosphate. This would suggest that ordering or modification of the conformation of residues in the lid domain of MTDHQase is important for increased catalytic activity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore we would expect that inhibition would not be as strong as that seen in the S. coelicolor enzyme. The presence of a second sulphate interacting with residues in part of the lid domain, in particular Arg19, a residue already shown to be important for catalysis [8], may help to explain the increase in V max seen in the presence of phosphate. This would suggest that ordering or modification of the conformation of residues in the lid domain of MTDHQase is important for increased catalytic activity.…”
Section: Discussionmentioning
confidence: 93%
“…The type II DHQases which have been kinetically characterised appear to fall into two groups. The enzymes from organisms such as S. coelicolor and Aspergillus nidulans have high relatively values of k cat , in the range 100–1000 s −1 at pH 7.0 and 25°C [2,8]. By contrast the enzymes from Helicobacter pylori , M. tuberculosis and Neurospora crassa have much lower values of k cat in the range 10 s −1 or lower [3,9–11].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the applications to primary structure analysis, recent approaches to the characterisation of higher-order (tertiary) structures, to structure-function studies and even specific non-covalent interactions of proteins are presently emerging as exciting new areas of mass spectrometry [3,5,11]; the recent discovery of ESI-MS as a tool for the direct analysis of supramolecular complexes and molecular recognition processes representing a major theme for this NATO conference [12,13]. Furthermore, the feasibility of soft-ionisation-MS methods to the analysis of multicomponent proteolytic mixtures (peptide mapping) has been demonstrated in several applications, and has been applied successfully to the molecular characterisation of chemical modification sites in proteins [14][15][16][17]. Since the initial studies employing the combination of specific protein-chemical modification reactions and mass spectrometric peptide mapping [3,14], useful structural information has been obtained already, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Tyr24 (M. tuberculosis numbering) is conserved amongst type II enzymes and is proposed to be the base responsible for the extraction of the axial pro-S hydrogen [61,73]. Site-directed mutagenesis experiments showed that Arg23 (S. coelicolor numbering, equivalent to Arg19 in MtDHQase) is an essential amino acid for catalysis [74], although its role is not totally clear as it is present in a flexible loop composed by residues 19-24 (MtDHQase numbering) and it seems to approximate Tyr24 after substrate-binding, lowering its pK a and starting the reaction [75]. It is worth noting that MtDHQase classification as type II is based on structural and theoretical predictions.…”
Section: -Dehydroquinate Dehydratase (Arod Coding Sequence; Ec 421mentioning
confidence: 99%